Análise textual discursiva sobre o multiculturalismo étnico racial presente na ciência - Andrade, Layla de Brito (Universidade Federal de São Carlos, 2025)
This research project addresses the intersection between multiculturalism and natural sciences, emphasizing the significance of ethnic and racial diversity in this context. Confronting substantial inclusion challenges, the field of natural sciences seeks a more inclusive and diversified approach in the 21st century. The study explores the relevance of multiculturalism in natural sciences, analyzing the impact of research on multiculturalism, with a focus on the ethnic and racial dimension. The adopted methodology is qualitative and descriptive, utilizing bibliographic research and discursive textual analysis. Selective reading and reflexive reading techniques will be employed to analyze the selected documents. It is expected that this project provides an in-depth understanding of how racial cultures are addressed in the context of natural sciences, highlighting existing gaps and challenges. The results obtained through discursive textual analysis will enable a critical and theoretical insight into the selected documents, offering perspectives to expand more inclusive content in natural sciences, contributing to the advancement of scientific knowledge, and promoting a more diverse and egalitarian environment.
Discursive textual analysis on ethnic-racial multiculturalism present in science
Keywords: Multiculturalismo; Ciências naturais; Educação; Diversidade étnico-racial; Inclusão; Análise textual discursiva; Multiculturalism; Natural sciences; Education; Ethnic and racial diversity; Inclusion; Discursive textual analysis; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM